PERANAN LATAR DALAM MEMBENTUK WATAK TOKOH DALAM NOVEL LUKISAN TANPA BINGKAI KARYA UGI AGUSTONO - Nurbaitiana, Nurbaitiana; Priyadi, Antonius Totok; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to determine the analysis of the role of the background in shaping the characters in novel Lukisan Tanpa Bingkai by Ugi Agustono J. The problems of this research are: (1) the role of the setting in shaping the character depicted in the novel Lukisan Tanpa Bingkai by Ugi Agustono J, (2) the role of the background time in shaping the character depicted in the novel Lukisan Tanpa Bingkai by Ugi Agustono J, (3) the role of the social settings in shaping the character depicted in the novel Lukisan Tanpa Bingkai by Ugi Agustono J, (4) the implementation of literary learning about the background in shaping the character. The purpose of this research is to describe the role of place, the role of time, and the role of sociality to create main characteristic.Â This study used a description method with qualitative research forms. The technique usedÂ this study documentary and data collection tool is the researcher himself as a key instrument. Based on the results of the analysis there are 23 the role of place, 14 the role of time, and 20 the role of sociality.Â Keywords: Role of Background, Novel